Dielectric and Magnetic Characterization of Sol-Gel Synthesized SrMnO3 Perovskite - Abbas, K.; Atiq, S.; Riaz, S.; Naseem, S. (The Nucleus, 2015)
Large exchange coupling has been reported in B-site magnetic perovskites which results in higher magnetic ordering temperatures. SrMnO3 is a perovskite manganite which has strong magnetostructural and magnetoelectronic effects such as colossal magnetoresistance, thus making it feasible in applications like magnetic sensors and information storage. Here we report a phase pure synthesis of SrMnO3 using sol-gel auto-combustion method. The crystal structure was optimized by sintering the prepared samples at temperatures like 400 °C, 600 °C, 800 °C, 1000 °C and 1200 °C for 4 hours. Structural studies through X-ray diffraction confirms the formation of perovskite SrMnO3. Dielectric studies were performed through impedance analyzer revealed the semiconducting behavior as the sintering temperature is raised. The magnetic study through vibrating sample magnetometer discloses enhancement of magnetization due to the ion displacement effect when the sintering temperature was changed.